Цитотаксономическое изучение циклопов группы Acanthocyclops "americanus-vernalis" (Crustacea, Copepoda) - Кочина, Е.М. (Вестник зоологии, 1987)
The new species differs from closely related Ch. constricta in larger rostellar hooks, achieving in the anterior row 0.0675-0.0730, in posterior row - 0.061-0.068 mm. It also differs from other related species - Ch. angolensis and Ch. isacantha. Ch. constricta is suggested to represent a collective taxon.